On the waves of the Amur – fascination with Russian songs, gusts of feelings and poetics transformations of Jonasz Kofta - Bednarczyk, Anna (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The author examines various types of transformations which a musical texts undergoes when it is introduced into a different culture. As the material for the analysis served poems of Jonasz Kofta, relying strongly on Russian motifs, Russian music and song lyrics. It turns out that the Polish version is not necessarily a translation: it may also be a parody, a completely new text or even a mystification.